2013
DOI: 10.1093/toxsci/kft226
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Hepatocellular Apoptosis Induced by Trovafloxacin-Tumor Necrosis Factor-alpha Interaction

Abstract: Idiosyncratic drug-induced liver injury (IDILI) continues to be a significant human health problem. IDILI is characterized as occurring in a minority of individuals exposed to a drug, yet it accounts for as much as 17% of all cases of acute liver failure. Despite these concerns, the mechanisms underlying IDILI remain unknown. Trovafloxacin (TVX), which causes IDILI in humans, also causes hepatocellular death in vitro when combined with tumor necrosis factor-alpha (TNF) treatment. However, the molecular mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 40 publications
5
43
0
Order By: Relevance
“…56 Another study also showed that TNF treatment could cause apoptosis and DNA damage in HepG2 cells. 57 In addition, we found a significant overlap between up-regulated proteincoding genes in prostate cancer and down-regulated genes after lnc-SNURF-1 knockdown (Fig. 7E, P = 0.0267), and a marginal significance between down-regulated protein-coding genes in prostate cancer and up-regulated genes in the knockdown data ( Fig.…”
Section: Systematic Evaluation Of Predicted Cancer-related Lncrnasmentioning
confidence: 73%
“…56 Another study also showed that TNF treatment could cause apoptosis and DNA damage in HepG2 cells. 57 In addition, we found a significant overlap between up-regulated proteincoding genes in prostate cancer and down-regulated genes after lnc-SNURF-1 knockdown (Fig. 7E, P = 0.0267), and a marginal significance between down-regulated protein-coding genes in prostate cancer and up-regulated genes in the knockdown data ( Fig.…”
Section: Systematic Evaluation Of Predicted Cancer-related Lncrnasmentioning
confidence: 73%
“…Toxicity was preceded by an increase and prolongation of TNF in the plasma of CPZ-LPS or CPZ-lipoteichoic acid coexposed animals, raising the possibility of a link between prolonged plasma TNF and hepatotoxicity, similar to what is observed during TVX-LPS coexposure. Another recent study described JNK-dependent cytotoxicity resulting from TVX/TNF coexposure in a hepatocyte cell line (Beggs et al, 2014). Therefore, it is possible that a common upstream stimulus in hepatocytes and macrophages activates JNK in response to TVX, and that this results in cell death in hepatocytes and increased cytokine release in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…JNK has been implicated in cell-death signaling, and examples of JNK dependence in drug-inflammation interaction models of hepatocellular injury have been described (Gandhi et al, 2013;Beggs et al, 2014). Chlorpromazine (CPZ) is a phenothiazine antipsychotic drug associated with IDILI in humans, and coexposure of rats to CPZ and LPS precipitates liver injury (Buchweitz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…5 cytes can be used and many compounds can be assessed in a screening assay with small amounts of compound. It has been reported that idiosyncratic DILI is closely related to mitochondrial dysfunction (Wang, 2014;Dykens et al, 2008;Boelsterli and Lee, 2014) and apoptosis of the hepatocytes (Beggs et al, 2014). In the present study, in order to establish an in vitro assay for the estimation of the potential risk of the idiosyncratic DILI, we employed a combination assay of two endpoints, mitochondrial dysfunction and apoptosis, using cryopreserved human hepatocytes as a new approach.…”
Section: Discussionmentioning
confidence: 99%
“…Trovafloxacin, which causes idiosyncratic DILI, induces hepatocellular apoptosis in vitro when tumor necrosis factor-α (TNF-α) is co-treated. TNF-α activates caspase cascade and leads to apoptotic cell death (Beggs et al, 2014).…”
Section: Introductionmentioning
confidence: 99%